PENGARUH KERAGAMAN MENU, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Konsumen Restoran D’Cost Seafood Semarang) - Savira Bintang Camelia; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The increasing number of alternative choice of restaurants in the city of Semarang cause competition getting tougher.As a result, many businesses that compete in the business of restaurants.D'cost seafood restaurant is one of the options in the city of Semarang. The number of restaurants that serves a similar menu variety at low prices caused the number of visitors D'Cost experience fluctuations from year 2014-2016. This is demonstrated by a decrease in the number of visitors by 2014 to 2015 of 0.2% and by 2015 to 2016 experienced increases of 2%.The purpose of this research is to know the influence of the diversity of the menu, the price and brand image against consumer purchasing decisions D'Cost Seafood. This research type is explanatory research. Sampling techniques using a purposive Sampling method.As for the number of samples taken as many as 100 respondents. Data were analyzed through the test validity, reliability test, correlation coefficient, crosstab, determination of the coefficient of linear regression, simple, multiple linear regression, t-test, F-test, and with the help of the program SPSS.Based on the results of the descriptive analysis, showed the results of research that the diversity of the menu are on various categories of 59.0 percent. Variable rates are at a sufficient category, amounting to 48.0 percent. Brand image is variable in quality, category of 74.0 percent and the variable purchase decisions are high on the category, for 57.0 percent. Multiple correlation coefficient calculation based on yield value of 0.695 which means to have a strong correlation. Based on the calculation of the coefficient of determination indicates that the variable is the diversity of the menu, prices, and brand image contributed to the influence of 48.3 per cent against a purchasing decision.Suggestion in this research areproviding new menu variations according to the wishes of consumers. Improve the quality of the product and provide cheap package price promotions are also very necessary. In addition, the necessity of observing the tagline of which belonged to the "Mutu Bintang Lima Harga Kaki Lima" because according to the perceptions of the respondents, the tagline does not correspond to reality.